2006
DOI: 10.1534/genetics.105.050625
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology in Drosophila Membrane Excitability Mutants

Abstract: Mutations affecting ion channels and neuronal membrane excitability have been identified in Drosophila as well as in other organisms and characterized for their acute effects on behavior and neuronal function. However, the long-term effect of these perturbations on the maintenance of neuronal viability has not been studied in detail. Here we perform an initial survey of mutations affecting Na 1 channels and K 1 channels in Drosophila to investigate their effects on life span and neuronal viability as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 94 publications
2
40
0
Order By: Relevance
“…3a-c). This is consistent with the findings that Fergestad et al, 2006). Paralysis in mle napts flies can be completely rescued by the addition of a single extra copy of the para + gene (Stern et al, 1990).…”
Section: Temperature-sensitive Paralysis Is Often Associated With Neusupporting
confidence: 89%
See 1 more Smart Citation
“…3a-c). This is consistent with the findings that Fergestad et al, 2006). Paralysis in mle napts flies can be completely rescued by the addition of a single extra copy of the para + gene (Stern et al, 1990).…”
Section: Temperature-sensitive Paralysis Is Often Associated With Neusupporting
confidence: 89%
“…The notion that sensitivity to ts paralysis reflects the level of neuronal function in flies is supported by the fact that extensive screens for ts paralytic phenotype have recovered a number of mutations in genes associated with neuronal function. Mutation in such genes is often associated with shorter lifespan and neurodegeneration (Fergestad et al, 2006). In addition, we propose that ts paralysis could be used as a biomarker of increased frailty and decline of neuronal function during aging in Drosophila.…”
Section: Temperature-sensitive Paralysis Is Often Associated With Neumentioning
confidence: 99%
“…Life-span analysis: Life spans were measured at 29°accord-ing to standard protocols as described previously (Kretzschmar et al 1997;Lin et al 1998;Min and Benzer 1999;Palladino et al 2002;Palladino et al 2003;Fergestad et al 2006b). In brief, newly eclosed animals were collected, separated by sex, placed in vials (up to 20 per vial), and transferred to fresh vials daily, and survivorship was recorded for each vial.…”
Section: Methodsmentioning
confidence: 99%
“…20 for each genotype). Neurodegeneration for each genotype was scored as previously described (Fergestad et al 2006b). Briefly, each genotype was assigned a score from 0 to 5 on the basis of the frequency and severity of vacuolar pathology observed in brain serial sections as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, an initial histological survey of our collection demonstrated that it was enriched for mutants with defects in neuronal survival: Ϸ10% of the mutants examined manifest varying degrees of age-dependent neuropathology in the central nervous system (17). Among the previously identified mutants associated with neurodegeneration are those encoding ion channels, the Na ϩ ͞K ϩ ATPase, and components of the synaptic release machinery (17)(18)(19).…”
mentioning
confidence: 99%